1997
DOI: 10.1246/cl.1997.953
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Ion Channel Formation of Novel Cyclic Peptides Containing a Non-natural Amino Acid

Abstract: A series of novel cyclic peptides possessing an alternate natural / non-natural amino acid sequence were prepared from l-alanine and 5-(N-acylamino)-3-aminobenzoic acid with a long acyl chain. Upon examination by the voltage clamp method, membranes composed of the synthetic cyclic peptides with varying ring sizes and side-chain lengths were found to form cation selective channels with a conductance of ca. 9 pS in aqueous KCl (500 mM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Using the same strategy, Ishida and co-workers reported ion channels formed by compounds of type 2, described as ''cyclic peptides containing an non-natural amino acid'' (3-amino-5-N-acylbenzoic acid). 36,37 Each of the individual elements were modified systematically: ring size (hexa-to deca-peptide), length of alkyl chain (10, 16, 18 carbons total), and amino acid side-chain on the macrocycle. Regular openings were observed for all of the compounds, and these openings were amenable to blocking by Ca 2+ ions.…”
Section: Circular Topology/macrocycle-basedmentioning
confidence: 99%
“…Using the same strategy, Ishida and co-workers reported ion channels formed by compounds of type 2, described as ''cyclic peptides containing an non-natural amino acid'' (3-amino-5-N-acylbenzoic acid). 36,37 Each of the individual elements were modified systematically: ring size (hexa-to deca-peptide), length of alkyl chain (10, 16, 18 carbons total), and amino acid side-chain on the macrocycle. Regular openings were observed for all of the compounds, and these openings were amenable to blocking by Ca 2+ ions.…”
Section: Circular Topology/macrocycle-basedmentioning
confidence: 99%
“…Based on this simple structural model the structure and function of the channel could be correlated. The peptide ring, with its rigid structure (Ishida et al, 1997) on one hand, provides a cavity for the entering of water and permeant ions into the pore and, with its hydrophilic feature on the other hand, forms the channel entrance at the membranewater interface and gives the binding site for ions. Consequently, the acyl chains line across the membrane form an ion-conducting pathway.…”
Section: Structural Modelmentioning
confidence: 99%
“…One way to do so is to take advantage of the simpler structure of the artificial ion channel to build a model channel system. Such model channels have been paid great attention (Sokabe et al, 1997) and developed by means of several different strategies: by employing the channel-forming antibiotics, such as the gramicidin channel (see Andersen and Koeppe, 1992 for review); by mimicking the sequence of the pore region of known channel proteins (Oiki et al, 1988a,b); or by de novo design (Lear et al, 1988;Kobuke et al, 1992;Tanaka et al, 1995;Ishida et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] UV-vis titration experiments in DMSO indicated that the disodium salt of 4-nitrophenyl phosphate forms 1 : 1 complexes with the receptors [K a = 1.2 Â 10 6 M À1 for cyclo-(Ala-Aba) 3 (4)]. Additional evidence for the binding mode was obtained by 1 H NMR spectroscopy, which indicates that 4 has C 3 -symmetry that is maintained on binding the phosphoester.…”
Section: Simple Cyclic Peptidesmentioning
confidence: 98%